From Conquerors to Enchanters: Ways of Apprehending Reality Through Novelistic Creation - Botnari, Larisa (Literatūra, 2022)
Creators of new worlds through their novels, André Malraux and Romain Gary equally reject the real universe – considered as odious, tragic, absurd – as well as any purely mimetic link between this universe and literary creation. But the two novelists translate this opposition into completely different registers. If Malraux’s writing seems to express the desire for a direct confrontation and defiance, Gary’s work is rather characterized by a mocking, disdainful attitude towards reality, which the writer intends to conquer mainly by humor. Our article aims to show that Gary’s literary response, far from being an escape, represents a rebellion that is just as powerful (and, in certain aspects, more relevant for our times) than the commitment and the fight explicitly assumed by Malrucian writing.
Keywords: reality; imagination; rebellion; aesthetics; contemporary